Hybrid Review: Research Trends Fe3O4-WTa37O95.487 Magnetic Nanocomposite as a Multifunctional Adsorbent for Decontamination of Industrial Dye Wastewater of Woven Fabrics - Susilawati; Muhammad Taufik; Teguh Ardianto; Syarful Annam (Jurnal Penelitian Pendidikan IPA, 2026)
The increasing discharge of dye-contaminated wastewater from the textile industry poses serious environmental and health challenges, necessitating the development of efficient, sustainable, and reusable treatment materials. This study presents a hybrid review integrating a Systematic Literature Review (SLR) and bibliometric analysis to critically examine research trends, material design strategies, adsorption mechanisms, and existing limitations of magnetic nanocomposite adsorbents for textile dye wastewater treatment. Following the PRISMA 2020 guidelines, 30 peer-reviewed articles published between 2018 and 2025 were systematically selected for SLR from Scopus and SINTA databases and 200-500 articles for bibliometric analysis. Bibliometrics focuses on Scopus data (to identify global trends), while SINTA is used to strengthen SLR in the local context of the Indonesian textile industry. Bibliometric mapping using VOSviewer reveals a growing research emphasis on multifunctional materials, regeneration performance, and sustainability, while the SLR highlights a dominant focus on binary nanocomposite systems and single-dye adsorption studies under idealized laboratory conditions. A significant research gap is identified in the integration of complex tungsten–tantalum oxide phases with magnetic Fe₃O₄ matrices. Addressing this gap, this review identifies the integration of complex tungsten–tantalum oxide phases as a promising future research direction to overcome current limitations in chemical stability and improved resistance to harsh textile wastewater environments. The findings provide strategic insights for the design of next-generation magnetic adsorbents with improved industrial applicability and environmental sustainability.